Macrophage MMP10 Regulates TLR7-Mediated Tolerance - Rohani, Maryam G.; Dimitrova, Elizabeth; Beppu, Andrew; Wang, Ying; Jefferies, Caroline A.; Parks, William C. (Frontiers in Immunology, 2018)
Using an in vivo model of tolerance to TLR7-induced skin inflammation, we found a critical role for macrophage-derived MMP10 in mediating immune hypo-responsiveness. Cutaneous exposure to Imiquimod (IMQ), a TLR7 agonist, induced acute expression of pro-inflammatory factors (IL1β, IL6, CXCL1) and neutrophil influx equally in both wildtype and Mmp10–/– mice. However, whereas subsequent exposure (11 and 12 days later) to IMQ led to marked abrogation of pro-inflammatory factor expression in wildtype mice, Mmp10–/– mice responded similarly as they did to the first application. In addition, the second exposure led to increased expression of negative regulators of TLR signaling (TNFAIP3, IRAK3) and immunosuppressive cytokines (IL10, TGFβ1) in wildtype mice but not in Mmp10–/– mice. In vitro studies demonstrated that prior exposure of IMQ to bone marrow-derived macrophages (BMDM) made wildtype cells refractory to subsequent stimulation but did not for Mmp10–/– macrophages. These findings expand the critical roles MMP10 plays in controlling macrophage activation to indicate that the development of immune tolerance to TLR7 ligand is dependent on this macrophage-derived proteinase.